2021
DOI: 10.1021/acs.chemrev.0c00522
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition in Water Using Macrocyclic Synthetic Receptors

Abstract: Molecular recognition in water using macrocyclic synthetic receptors constitutes a vibrant and timely research area of supramolecular chemistry. Pioneering examples on the topic date back to the 1980s. The investigated model systems and the results derived from them are key for furthering our understanding of the remarkable properties exhibited by proteins: high binding affinity, superior binding selectivity, and extreme catalytic performance. Dissecting the different effects contributing to the proteins' prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
153
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(178 citation statements)
references
References 359 publications
(1,221 reference statements)
4
153
0
1
Order By: Relevance
“…Thus, we have demonstrated that (i) conjugate 2 can serve as a precursor to MPTTF-calix [4]arene molecular tweezers with different substituents on the calixarene lower rim and (ii) propargylated derivative 4 can be modified using the click reaction with various substituents bearing an azide group, which makes compound 4 another universal precursor in the synthesis of modified MPTTF-calix[4]arene receptors. In future, functionalities attached to the lower rim can be used, for example, for solubilization of the receptors in aqueous media [20] or for their attachment onto surfaces e. g. for sensing applications. [21] Electrochemical properties of new bis-MPTTF molecular tweezers have been investigated by means of cyclic voltammetry (CV) in dichloromethane/Bu 4 NClO 4 solution (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we have demonstrated that (i) conjugate 2 can serve as a precursor to MPTTF-calix [4]arene molecular tweezers with different substituents on the calixarene lower rim and (ii) propargylated derivative 4 can be modified using the click reaction with various substituents bearing an azide group, which makes compound 4 another universal precursor in the synthesis of modified MPTTF-calix[4]arene receptors. In future, functionalities attached to the lower rim can be used, for example, for solubilization of the receptors in aqueous media [20] or for their attachment onto surfaces e. g. for sensing applications. [21] Electrochemical properties of new bis-MPTTF molecular tweezers have been investigated by means of cyclic voltammetry (CV) in dichloromethane/Bu 4 NClO 4 solution (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion geometry of the 52 4+ complex diminishes the aromatic surface of the receptor available to water solvation. Because the binding of non-polar residues in water is mainly driven by the hydrophobic effect (HE), 38,43 the reduction in aromatic surface helps explain the lower aggregation tendency of the 52 4+ complex compared to the free receptor 2 4+ . The addition of ca.…”
Section: Self-assembly Of the [2•pd] 6+ CC In The Presence Of Pyridine Noxide Guestsmentioning
confidence: 99%
“…All the polar guests used are difficult to bind in water solution with other synthetic receptors. 38,39,40 Using 1 H NMR spectroscopy, we study the conformational arrangement adopted by the end formyl groups of the α,ω-bis-formamides included in the [2•Pd] 6+ CC. We disclose solid-state structures for analogous inclusion complexes with the organic-soluble [1a•Pd] 2+ CC.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated large and negative heat capacity values (DC p )f or all binding processes.T his result indicates that the formation of the complexes, 2b-4b&1,i sm ainly driven by the hydrophobic effect. [34,35] Based on the above,w eh ypothesized that in the 2b&1 complex, the rate of the hydrolysis reaction producing the mono-formamide 3b should be different from that in the bulk solution.…”
Section: Angewandte Chemiementioning
confidence: 99%